Utilization of Interphalangeal Joint Arthroplasty and Arthrodesis in the United States From 2010 to 2019 - Erica L. Smearman, MD, PhD; Anthony L. Karzon, MD; Hayden L. Cooke, BS; Zaamin B. Hussain, MD, EdM; Musab Gulzar, BS; Nina Suh, MD; Michael B. Gottschalk, MD; Eric R. Wagner, MD, MS (Plastic and Reconstructive Surgery, Global Open)
Background:. Interphalangeal joint (IPJ) arthrodesis and arthroplasty are mainstay treatments for IPJ arthritis with conflicting evidence about the most efficacious choice. Our study describes case volume and incidence over the last decade (2010–2019). Methods:. The IBM MarketScan database was queried using Current Procedural Terminology codes for IPJ arthrodesis and arthroplasty from January 2010 to December 2019. Volume and incidence were estimated annually and according to sex, age, and US geographical region for 2010 and 2019. Results:. Annual volume and incidence of IPJ arthrodesis increased slightly from 2010 to 2019, though with overlapping confidence intervals for incidence. Arthrodesis tended to be higher in women versus men, especially with increasing age. When considering age, the most substantial increase in rates over increasing age was moving from the 40s to 50s age brackets. Across US regions, arthrodesis was higher in the northeast and midwest in 2010, though other rates rose and regions were similar by 2019. For IPJ arthroplasty, there was a 25%–30% decrease in case volume and incidence over the decade. Incidence was generally higher among women, with a similar jump in incidence from 40s to 50s among women, whereas men showed a more gradual rate increase with age. Regionally, arthroplasty was highest in the northeast and midwest in 2010, though it was similar across regions in 2019. Conclusions:. Although IPJ arthrodesis levels have stayed relatively stable, IPJ arthroplasty showed a general decline over the decade. Incidence of both were higher among women, and despite initial regional differences, rates became more similar by 2019.